2021
DOI: 10.3390/plants10071445
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Constituents and Allelopathic Potential of Parthenium hysterophorus L. in Comparison to Commercial Herbicides to Control Weeds

Abstract: The allelopathic effect of various concentrations (0, 6.25, 12.5, 50 and 100 g L−1) of Parthenium hysterophorus methanol extract on Cyperus iria was investigated under laboratory and glasshouse conditions. No seed germination was recorded in the laboratory when P. hysterophorus extract was applied at 50 g L−1. In the glasshouse, C. iria was mostly injured by P. hysterophorus extract at 100 g L−1. The phytochemical constituents of the methanol extract of P. hysterophorus were analyzed by LC-ESI-QTOF-MS=MS. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Our results are consistent with previous research, which reported that Senna species have inhibitory activity, such as extracts of S. obtusifolia and S. occidentalis causing the inhibition of the seed germination and growth of plant species [7,8]. Moreover, the unequal susceptibility of the tested species to the extracts could be due to inherent differences in the biochemicals involved in the process [34]. The species specificity of phytotoxic substances has also been demonstrated for other allelopathic plant species [35][36][37].…”
Section: Resultssupporting
confidence: 92%
“…Our results are consistent with previous research, which reported that Senna species have inhibitory activity, such as extracts of S. obtusifolia and S. occidentalis causing the inhibition of the seed germination and growth of plant species [7,8]. Moreover, the unequal susceptibility of the tested species to the extracts could be due to inherent differences in the biochemicals involved in the process [34]. The species specificity of phytotoxic substances has also been demonstrated for other allelopathic plant species [35][36][37].…”
Section: Resultssupporting
confidence: 92%
“…At 35 DAS, T 2 (2691.00 L ha −1 WeedLock) produced 51.38%, while T 4 (4 L ha −1 glyphosate isopropyl-amine) and T 6 (4 L ha −1 glufosinate-ammonium) exhibited 66.47% and 66.05% weed control efficiency, respectively. Plant-based bioherbicides may involve protein synthesis and decreased protein binding of chlorophyll a/b two-fold, affecting photosynthesis by the suppressing of chlorophyll synthesis [37,38]. Plant-based bioherbicides reduce the biosynthesis of Oxygen evolving enhancer protein 1, and it influences gas and nutrient exchange in weed species [39].…”
Section: Discussionmentioning
confidence: 99%
“…Quantum yield (Fv/Fm). Quantum yield was measured for the newest fully expanded leaf of test plants at 10-12am using a portable plant efficiency analyzer (Model FMS 2, Hansatech Instrument Ltd. UK) 31 .…”
Section: Methodsmentioning
confidence: 99%